2014
DOI: 10.1007/s12010-013-0707-z
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Profiling of Zingiber zerumbet Following Pythium myriotylum Infection: Investigations on the Defensive Role of the Principal Secondary Metabolite, Zerumbone

Abstract: Induced biosynthesis of bioactive secondary metabolites constitutes one of the mechanisms of plant basal innate immunity to fungal infection. Metabolic changes were studied in rhizomes of Zingiber zerumbet, a wild congener of ginger, after infection with soft rot-causative necrotrophic phytopathogen, Pythium myriotylum, by gas chromatography-mass spectrometry (GC-MS) analysis. Infection triggered a considerable alteration in the relative content of zerumbone and α-caryophyllene (humulene) with enhancement in z… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…The beneficial properties of zerumbone extend to other areas, such as the agri-food industry [ 40 ] ( Figure 2 ). For example, Keerthi et al observed that the concentration of zerumbone increases in Z. zerumbet when infected with the rot-causative necrotrophic phytopathogen Pythium myriotylum , exhibiting natural resistance against the contamination [ 115 ] ( Figure 2 ). Furthermore, this molecule has shown promising antifungal activity against the other phytopathogenic fungi Aspergillus spp.…”
Section: Further Uses Of Zerumbonementioning
confidence: 99%
“…The beneficial properties of zerumbone extend to other areas, such as the agri-food industry [ 40 ] ( Figure 2 ). For example, Keerthi et al observed that the concentration of zerumbone increases in Z. zerumbet when infected with the rot-causative necrotrophic phytopathogen Pythium myriotylum , exhibiting natural resistance against the contamination [ 115 ] ( Figure 2 ). Furthermore, this molecule has shown promising antifungal activity against the other phytopathogenic fungi Aspergillus spp.…”
Section: Further Uses Of Zerumbonementioning
confidence: 99%
“…Comparison of bioactivity data permits early stage dereplication. This method also gives information about possible synergistic effects between molecules [52][53][54][55][56][57][58].…”
Section: Isolation and Characterization Of Bioactive Compoundsmentioning
confidence: 99%